2015
DOI: 10.3171/2014.9.spine1457
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of modified lumbar spinous process–splitting laminectomy for lumbar spinal stenosis

Abstract: The lumbar spinous process–splitting laminectomy (LSPSL) procedure was developed as an alternative to lumbar laminectomy. In the LSPSL procedure, the spinous process is evenly split longitudinally and then divided at its base from the posterior arch, leaving the bilateral paravertebral muscle attached to the lateral aspects. This procedure allows for better exposure of intraspinal nerve tissues, comparable to that achieved by conventional laminectomy while minimizing damage to posterior supporting stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…We do not have long-term follow-up information, but the results reported in the literature have been very favorable and stimulated the introduction of this technique into our field of activity. 2,3,7,8 The efficacy of the surgical treatment of lumbar canal stenosis has been well-evidenced in prospective, randomized studies 9,10 and it has been established that decompression of the vertebral canal, lateral recess, and vertebral foramen promote the improvement of symptoms. However, there are potential risks arising from the conventional surgical procedure involving open dissection with displacement and retraction of the paravertebral muscles, resection of the vertebral lamina, facet joints, spinous process, and injury to the posterior ligament structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not have long-term follow-up information, but the results reported in the literature have been very favorable and stimulated the introduction of this technique into our field of activity. 2,3,7,8 The efficacy of the surgical treatment of lumbar canal stenosis has been well-evidenced in prospective, randomized studies 9,10 and it has been established that decompression of the vertebral canal, lateral recess, and vertebral foramen promote the improvement of symptoms. However, there are potential risks arising from the conventional surgical procedure involving open dissection with displacement and retraction of the paravertebral muscles, resection of the vertebral lamina, facet joints, spinous process, and injury to the posterior ligament structures.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Performing less invasive surgeries with lower morbidity has been one of the goals of modern spine surgery and the spinous process splitting technique has been highlighted for its technical simplicity and reports of good results from its application. 3,7 The objective of this study was to observe the preliminary clinical and radiographical results from the use of the technique of spinal canal decompression by means of the approach using longitudinal splitting of the spinous process in patients with spinal canal stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…These have included a brief description of the technique and reports on the clinical outcomes in patients with lumbar canal stenosis. [14][15][16][17][18][19][20][21][22][23][24][25] Watanabe et al 14 compared the clinical outcomes at a minimum of 2 years between 18 patients treated with spinous process-splitting laminectomy and 20 patients treated with conventional laminectomy for lumbar canal stenosis. They concluded that comparable clinical results can be achieved for both techniques based on the Japanese Orthopaedic Association (JOA) score.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results suggested excellent decompression with less muscular damage than both traditional and other tubular techniques to decompress the lumbar spine. [14][15][16][17][18][19][20][21][22][23][24][25] The current authors theorized that this would be similar in a group of North American patients and therefore set out to analyze the results of a cohort of patients undergoing this procedure at their institution. The central hypothesis of this study was that spinous process-splitting laminoplasty is effective for the treatment of lumbar canal stenosis.…”
mentioning
confidence: 99%
“…It is associated with compression of the dural tube and spinal nerve root, and degenerative alteration in the lumbar spine. Various minimally invasive laminectomies have recently been introduced in patients with LSS, including bilateral decompression via the unilateral approach using a microendoscope and tubular retractor [1][2][3], lumbar muscle-preserving interlaminar decompression [4], and lumbar spinous process-splitting laminectomy (LSPSL) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%